How Did You Get Pregnant? A Gamified Culturally Sensitive Interview Protocol for Teenage Pregnancy victims in Sarawak Borneo - Fatahyah, Yahya; Fitri Suraya, Mohamad (Webology Center, 2022)
As an effort to understand the alarming increase in teenage pregnancy in Sarawak Borneo, the study focuses on determining socio-cultural and psychological factors which contribute toward pregnancies among young girls. Collecting stories and narrative data on issues that are deemed sensitive and hidden were the known challenges of the study. An interview protocol was developed to enable the extraction of stories and information from a group of protected young women who have experienced pregnancies at a young age and currently living under protective custody. The instrument consists of six main sections – Respondent’s background, presenting the case, cognitive stage of the respondent, emotional stage of the respondent, attachment with family members and future planning. Using locally known socio-cultural beliefs and values surrounding the concept of pregnancy, gamifying the protocol was a necessary approach in the design phase, to allow for ease-of-use, efficiency, memorability, and subjective satisfaction in collecting sensitive data. The paper explains the design process which highlights the empathetic considerations which relate to local cultural beliefs and values.